The Study of English Style: British English and American English Words - Jaya, Made Suardika (Institut Hindu Dharma Negeri Denpasar, 2020)
The British English and American English are most commonly used; which are usually referred as two â€˜mainâ€™ accents for the English language. Both of them are having their own uniqueness and characteristics in terms of word choices. When the speaker utters the words in one particular accent, by some means the listener could recognise which English style is the speaker more familiar with. To obtain the data of which English style are the speaker more familiar with, a straightforward study was held.Â The respondents for this study are ten people who live in the city of Singaraja with various ages and social backgrounds. They are requested to determine which English words are more familiar for them by showing them a table of words list. Fine comprehension about English in cooperation with the vocabularies that the respondents have will lead them to English style that fits them in four English proficiencies